Adaptation of Sumudu Transform Iterative Method for Solving Fractional IntegroDifferential Equations - Abuteen, Eman (AIUB Journal of Science and Engineering (AJSE), 2022)
-In this paper, we discussed a new Sumudu transform iterative method and successfully applied on linear and nonlinear fractional integro-differential equations. The obtained results are compatible with those that got by other methods. A comparison between our method and other results is given. The fractional derivative here described in the Caputo sense. The proposed method has the power by reducing the size of calculations and by finding the exact solution.